Behavioral Aspects of Organizational Team Performance and Commitment - Norzie Fariza, Suid (2004)
The purpose of this study was to investigate the culture, team performance and job satisfaction and how it affects the level of organizational commitment. Also examined was the influence of relationship of organizational commitment to demographic variables such as age, nationality, gender, marital status, education qualification, position, length of service and salary. Questionnaires contain of five sections-demographic factor; culture; job satisfaction; team performance and organizational commitment were used to collect data. In the demographic section, data solicited include age, nationality, gender, marital status, education qualification, position, length of service and salary. In thc culture section, data collection was based on Hofstede instruments; individualism/collectivism; uncertainty avoidance; masculinity and power distance. The questionnaires on the other two constructs, job satisfaction and team performance were adapted from original authors. In organizational commitment section, the instrument used was based on three themes identified by Allen and Meyer; affective organizational, continuance organizational and normative organizational. The data were analyzed using SPSS 11.5. Five main hypotheses were tested using T-test, one-way ANOVA and regression analysis. From the result it was found that culture and job satisfaction has significant difference to organizational commitment.